Unterrichtsfachsprache: Zur interaktionalen Normierung von Sprache im Mathematikunterricht der Grundschule (mathematica didactica, 2021)
To talk about mathematical contents, students and teachers do not use ‚the‘ technical language in mathematics lessons. In fact, they negotiate their own version of mathematical language and the corresponding rules of language use. In that process, opportunities and barriers for individual mathematical learning arise on a social plane. In this article, two types of linguistic norms in mathematics lessons are presented. The data was collected insecond grade classes and analyzed with interpretative methods.